Study on suppression of bituminous coal explosion by inert powder in cylindrical space - Tianqi Liu; Xingchen Wu (Case Studies in Thermal Engineering)
In order to understand how to control the spread of bituminous coal explosion, a cylindrical explosion tube is used for research. The results indicate that within 60 ms, the flame develops to the top of the tube. When 10 % inert powder is mixed in, the flame spreads to 1.2 cm at 10 ms, which is 0.4 cm shorter than the spread distance without adding inert powder. The time point for ending preheating and entering heating will be advanced with the increase of the mass of inert dust added. As the proportion of inert dust mixed decreases, the maximum impact airflow velocity of explosion gradually increases, the acceleration time interval gradually extends. When 10 % inert powder is mixed in, the maximum impact airflow velocity is 17 m/s, but it is delayed to 52 ms. The mixing of inert dust can reduce the mass fraction of CO inside the tube without changing the mass fraction of other gases, especially O2. As the mass of inert dust increases, the mass fraction of CO2 gradually increases and the range gradually expands.